2022
DOI: 10.7554/elife.78565
|View full text |Cite
|
Sign up to set email alerts
|

Starting to have sexual intercourse is associated with increases in cervicovaginal immune mediators in young women: a prospective study and meta-analysis

Abstract: Background:Adolescent girls and young women (AGYW) are at high risk of sexually transmitted infections (STIs). It is unknown whether beginning to have sexual intercourse results in changes to immune mediators in the cervicovaginal tract that contribute to this risk.Methods:We collected cervicovaginal lavages from Kenyan AGYW in the months before and after first penile-vaginal sexual intercourse and measured the concentrations of 20 immune mediators. We compared concentrations pre- and post-first sex using mixe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…To uncover the reasons for this vulnerability, we examined changes in cervicovaginal immune mediators after first-time intercourse in a cohort of adolescent girls and young women in Kenya. 134 We found that all 19 immune mediators that were consistently detectable increased postfirst sex, and then rose further over the following year, with the highest statistical significance for IL-1β, IL-2, and CXCL8. Taken together, FRT immunity clearly changes within individuals over time, influenced by sex hormones, age, and behavior.…”
Section: Defining T Cell Fun C Ti On In the H Uman Frt-accounting For...mentioning
confidence: 63%
See 1 more Smart Citation
“…To uncover the reasons for this vulnerability, we examined changes in cervicovaginal immune mediators after first-time intercourse in a cohort of adolescent girls and young women in Kenya. 134 We found that all 19 immune mediators that were consistently detectable increased postfirst sex, and then rose further over the following year, with the highest statistical significance for IL-1β, IL-2, and CXCL8. Taken together, FRT immunity clearly changes within individuals over time, influenced by sex hormones, age, and behavior.…”
Section: Defining T Cell Fun C Ti On In the H Uman Frt-accounting For...mentioning
confidence: 63%
“…The period spanning months immediately after first‐time penile‐vaginal sexual intercourse is associated with higher incidences of STIs and bacterial vaginosis compared to later in life. To uncover the reasons for this vulnerability, we examined changes in cervicovaginal immune mediators after first‐time intercourse in a cohort of adolescent girls and young women in Kenya 134 . We found that all 19 immune mediators that were consistently detectable increased postfirst sex, and then rose further over the following year, with the highest statistical significance for IL‐1β, IL‐2, and CXCL8.…”
Section: Defining T Cell Function In the Human Frt—accounting For Sex...mentioning
confidence: 97%
“…Excess sleep, partial sleep, insufficient sleep, and sleep deprivation, as well las frequent and infrequent napping, have all been associated with an increase in (hs)CRP concentrations [ 1067 , 1068 ]. Even if most studies have found that sex can modulate systemic inflammation, there also exist contrasting data highlighting that frequent sex can affect inflammatory markers [ 1069 ]. Apart from some previously discussed psychological conditions and cognitive decline, lower IQ levels in youth have been linked to low-grade systemic inflammation, whereas an interesting study demonstrated that daily discrimination, but not direct microaggressions based on sexual orientation, were linked to higher levels of CRP among young sexual-minority men, highlighting the immune vulnerability of the LGBT+ community [ 1070 , 1071 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…Для дослідження і клінічного аналізу кровігемограми -виконано забір венозної крові в пробірку об'ємом 1,0 мл з антикоагулянтом (етилендіамінтетраоцтовою кислотою -ЕДТА). Для виконання імунограми проведено забір крові в пробірку об'ємом [3][4] Зміни середньої сироваткової концентрації молекули IgA були схожими на такі в IgE (рис. 1В).…”
Section: матеріали та методи дослідженняunclassified
“…Відповідно до цього з'ясовано, що розлади функціонування імунної системи асоційовані з порушенням складу вагінального мікробіому і є важливими чинниками ризику формування НЗЗЖСО. Однак остаточно механізми зв'язку мікробіому піхви з регуляторними системами організму хазяїна досі не з'ясовані і є об'єктом активних наукових досліджень останніх років [4]. Особливу увагу серед багатьох аспектів зазначеної взаємодії надають саме імунному нагляду, з порушеннями якого пов'язують як феномен вагінального дисбіозу, так і розвиток власне НЗЗЖСО.…”
unclassified